Usefulness of human security concept: African perspective - Messash Kassaye Woldetsadik (Cхід, 2018)
This article is devoted to analysis the value of the human security concept to African nations. The value of the concept is examined in seven different ways. First, it sends a message to state politicians that their responsibility goes beyond state sovereignty. Second, it creates shared responsibility towards local and regional peace and security. Third, it brought improvement in socio-economic aspects. Fourth, it launches diversified responses to achieve conflict agenda. Fifth, it asserts accountability is at the corner for any wrong doings. Sixth, it allows AU and decision making bodies of sub-regional organizations and states to make informed decision based on research and thorough analysis. Seventh, it is pushing Africans to find alternative source of funding. In general, it should be noted that the use of the concept of human security ensures adequate social transformations in modern Africa